Australian patient perspectives on the impact of gout. (10th August 2020) - Coulshed, Andrew; Nguyen, Amy D.; Stocker, Sophie L.; Day, Richard O.
Abstract: Objective: To explore the perceptions of patients toward the impacts of gout, in an Australian context. Methods: Semi‐structured interviews were conducted with Australian patients with gout (n = 17). Interviews focused on the impacts of gout on patients' day‐to‐day lives. The interviews were audio‐recorded, transcribed verbatim and analyzed thematically by 2 independent reviewers. Results: Patients with gout reported variable but significant impacts of gout on their daily lives. Patients were primarily concerned with the pain and poor mobility associated with gout flares. Participants also reported significant social impacts related to their inability to attend events and the need for family and friends to look after them. Productivity was also negatively affected due to pain and poor mobility, and emotional wellbeing was reduced both by the symptoms of gout flares and anxiety between flares. Diet, daily planning, hobbies, exercise, sleep and selection of attire were also reported as being impacted by their gout. Conclusions: In Australia, gout has significant and preventable impacts beyond the physical symptoms of gout flares, across a variety of domains. By identifying patients' key concerns, this can potentially aid clinicians to tailor gout education and encourage medication adherence, in order to improve gout management.